2015
DOI: 10.1177/0193723515615177
|View full text |Cite
|
Sign up to set email alerts
|

Football Fans’ Views of Violence in British Football

Abstract: 1 Football Fans' Views of Violence in British Football: Evidence of a Sanitized and Gentrified CultureThis article draws on the responses of 1,500 fans from across the United Kingdom to an online survey posted from August 2013 to November 2013 regarding their experience of football violence. Reflecting the 2013 Home Office report that indicated a continued long-term decline of football fan violence in England and Wales, 89% of fans illustrate a decrease in violent behavior from the 1980s with 56% indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…Previous research had observed that overt forms of racism and racist violence in football stadia, initiated by football fans typically on the far-right, was seemingly in decline in the 2000s (Kassimeris 2007, p. 86), leading to what some have interpreted as a more 'sanitised' and less violent fan culture (Cleland and Cashmore 2016). However, this 'decline', owing in some part to a number of anti-racist campaigns -Fans for Diversity, a joint initiative launched in 2014 and run by the Football Supporters Federation and Kick It Out, being one such example in England -has not naturally translated into a significant increase in BAME fans on the terraces at men's professional games.…”
Section: Critical Race Theory Whiteness and Football Fandommentioning
confidence: 99%
“…Previous research had observed that overt forms of racism and racist violence in football stadia, initiated by football fans typically on the far-right, was seemingly in decline in the 2000s (Kassimeris 2007, p. 86), leading to what some have interpreted as a more 'sanitised' and less violent fan culture (Cleland and Cashmore 2016). However, this 'decline', owing in some part to a number of anti-racist campaigns -Fans for Diversity, a joint initiative launched in 2014 and run by the Football Supporters Federation and Kick It Out, being one such example in England -has not naturally translated into a significant increase in BAME fans on the terraces at men's professional games.…”
Section: Critical Race Theory Whiteness and Football Fandommentioning
confidence: 99%
“…Consequently, future research may conceptualize collective violence around the motivations for violence identified in the QVT and/or the recently proposed initiation-escalation model of public disorder, which argues that collective violence may also arise by the mere presence of a rival group (Adang 2011). The fact that groups known for their frequent participating in collective violence are also involved in arranging confrontations with like-minded groups (Cleland and Cashmore 2016) further substantiates this reasoning.…”
Section: Discussionmentioning
confidence: 83%
“…Although Friman et al (2004) advocate that similar hostilities are typically the result of others lacking knowledge of football rules, due to the nature of his miss-treatment, it may be effective to associate the supporter actions with confrontational spectator's behaviour normalised in professional football (i.e. modern fan culture) (Cleland & Cashmore, 2016;Razavi et al, 2014;Slabbert & Ukpere, 2010).…”
Section: Reflectionsmentioning
confidence: 99%